Statyka Podłużnie Niejednorodnej Płyty Reissnera o Zmiennej Grubości - Gawęcki, A. (Engineering Transactions, 1972)
The fundamental equations of the problem indicated in the title are obtained by means of the E. Reissner variational theorem applied to the orthotropic, linearly elastic body. The equations are written in terms of displacements, the unknown functions being the following three averaged displacements: two angles of rotation of the linear elements normal to the middle surface of the plate and its deflection. The displacement equations form a coupled system of linear partial differential equations with variable coefficients. Analysis of the boundary value problem yields 8 variants of homogeneous boundary conditions.